2010
DOI: 10.1111/j.1440-169x.2010.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblasts protect myoblasts from intrinsic apoptosis associated with differentiation via β1 integrin‐PI3K/Akt pathway

Abstract: Skeletal myoblasts withdrawing from cell cycle is a prerequisite for myodifferentiation, while upon proliferation ⁄ differentiation transformation, a large portion of myoblasts will undergo apoptosis. Skeletal fibroblasts, residing in muscle tissue both during and post myogenesis, have been proofed to play pivotal roles in muscle development, while their effect on myoblast apoptosis being coincident with differentiation has not been reported. Using a membrane insert co-culture system, we studied it and found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
0
10
1
Order By: Relevance
“…In vivo studies suggest that ablation of fibroblasts leads to depletion of satellite cells, premature satellite cell differentiation, and results in smaller regenerated myofibers (36). In vitro studies have shown that increasing fibroblasts in co-culture also promotes the migration of myoblasts (18) and that fibroblasts protect myoblasts from apoptosis during differentiation, promoting myotube formation (37). This agrees with our current studies showing that the presence of fibroblasts increases myoblast cell numbers and migration.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo studies suggest that ablation of fibroblasts leads to depletion of satellite cells, premature satellite cell differentiation, and results in smaller regenerated myofibers (36). In vitro studies have shown that increasing fibroblasts in co-culture also promotes the migration of myoblasts (18) and that fibroblasts protect myoblasts from apoptosis during differentiation, promoting myotube formation (37). This agrees with our current studies showing that the presence of fibroblasts increases myoblast cell numbers and migration.…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence has been provided for the control of AKT activity by integrins [48]. Particularly, ILK has been demonstrated to have a strong effect on Ser-473 phosphorylation of AKT [49].…”
Section: Discussionmentioning
confidence: 99%
“…PIK3R1 and FST are not only target genes of E2F1 (8), but also important members of signal pathways that regulate myogenesis. It has been shown, using C2C12 myoblasts, that the PI3K pathway regulates the myoblast migration (20), proliferation (21,36), differentiation (21,40,53,55,67), and fusion (52), as well as increase of myotube size (28, 48) during myogenesis. PIK3R1 is a subunit of PI3K pathway, affecting muscle development and growth in zebrafish and mouse (37,41).…”
Section: Discussionmentioning
confidence: 99%